THE ENCOURAGEMENT OF MARRIAGE IN THE QURANIC EXEGESIS: A COMPARATIVE STUDY OF TAFSĪR AL-ṬABARĪ, AL-KASHSHĀF, AND FĪ ẒILĀL AL-QUR'ĀN - Kamil, Fajri; Muhajirin, Muhajirin; Alkaf, Idrus (ILMU USHULUDDIN, 2024)
This study aims to compare the interpretations of verses recommending marriage by exegetical scholars who lived as bachelors. The research will identify differences in their interpretations and assess whether their status as bachelors influenced their interpretations, potentially creating bias. The methodology used is qualitative research with content analysis, utilizing primary data sources from the tafsīr works of al-Ṭabarī, al-Zamakhsharī, and Sayyid Quṭb, as well as secondary data from other supporting literature. This study employs two approaches: a methodological and a theoretical approach. Methodologically, the study uses the methods of comparative exegesis (tafsīr muqarān), thematic exegesis (tafsīr mauḍū’ī), and analytical exegesis (tahlīl), while also applying both textual and contextual approaches. Theoretically, the study applies the principles of exegesis (al-dakhīl fi tafsīr). The findings of this study indicate that there are differences in the interpretation of verses recommending marriage among the exegetes who lived as bachelors. The interpretations of al-Ṭabarī and Sayyid Quṭb on marriage-related verses were not influenced by their status as bachelor scholars. However, al-Zamakhsharī’s interpretation of the same verses appears to have been influenced by his condition as a bachelor scholar.